VALIDITAS DAN RELIABILITAS INSTRUMEN PENGETAHUAN PEMBELAJARAN AKTIF, KREATIF DAN MENYENANGKAN (PAKEM) MENGGUNAKAN MODEL RASCH - Salma Hayati; Lailatussaadah Lailatussaadah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2016)
Instruments of Active, Creative, Effective and Fun learning (PAKEM) were created to measure teachers' knowledge about the PAKEM’s concept as a form of learning strategies implemented in teaching in schools and madrasahs. This study was conducted to produce empirical evidence on the validity and reliability of the PAKEM instrument using the RaschMeasurement Model analysis. A Survey study has been conducted on 30 teachers fromMadrasah Ibtidaiyah School (MI) in the Aceh Districts. The validity and reliability of the PAKEM instrumentswere tested with the Rasch.Measurement Model analysis usingthe Winsteps program. The unidimensionality test conducted showed standarlized residual variance of 37.9 % which is almost to the point of at least 40.0 % points desired by Rasch models . The Rasch Model analysis showed person reliability index of 0.77 and the item reliability index of 0.88 . In terms of polarity items showed that all the items have value Point Correlation Measure ( PMC ) positive means there is no conflict between the items and the constructs being measured . Value Mean Square also showed that all the items have a mean square less than 1.5 , which means the value of the measurement of productive unless the item Peng10 (2.21) and item Peng1 (3.88). For both of these items need to be re- examined because it has a problem in measuring validity. The results of this study have proved that PAKEM instrument has a standard value of validity and reliability to be usedin measuring knowledge PAKEM strategis for teachers.